RELIGIOUS DUTY BOUND IN SAFEGUARDING THE COUNTRY: Assessing the Role of Nahdlatul Ulama in Peace Education in Jakarta - Uksan, Arif; Prihantoro, Mitro (State Islamic University (UIN) of Sunan Ampel Surabaya, 2025)
Jakarta, the capital of Indonesia is a religiously plural region in Indonesia that experienced social unrest and riots in recent history. It withstands social, economic and turmoil that Indonesia experience during its lifetime until today. As a country with Muslims as majority, the role of Islam and Muslims is instrumental in keeping it safe and endured. This study analyzes the role of Nahdlatul Ulama in peace education, using a qualitative descriptive method. As the biggest Muslim organization in Indonesia with moderate stance, the importance of strengthening peace education by Nahdlatul Ulama is certainly beyond any doubt. The study shows that Nahdlatul Ulama promoted its moderate values to its members and Jakarta populations as well as introduced many initiatives to contain exclusive understanding of Islam. It does not only in accordance with the message of peace by Islam as promoted by Nahdlatul Ulama, but from security perspective it contribute to national security greatly as well.